In vitro toxicity and control of Meloidogyne incognita in soybean by rosemary extract - Mônica Anghinoni Müller (Semina: Ciências Agrárias, 2016)
The control of nematodes in plants can be challenging, and there is a need for alternative, environmentally conscious methods for their management. The purpose of this study was to evaluate the effect of rosemary extract (Rosmarinus officinalis) on the in vitro toxicity and control of Meloidogyne incognita in CD 206 and CD 215 soybean cultivars. Using an in vitro assay, 500 M. incognita eggs per plate were observed for 15 days after incubation with rosemary extract at concentrations of 1%, 5%, and 10%. Soybean plants were studied under greenhouse conditions, and starting at V3 stage, were sprayed weekly with the same concentration of rosemary extract for 64 days. Three days after the first treatment, each soybean plant was inoculated with 1800 eggs and 400 second-stage juveniles (J2). At the end of this essay, number of eggs and J2 in the roots and soil, number of galls, and the reproduction factor (RF) were evaluated. Our results showed that in the in vitro assay, rosemary extract reduced the number of M. incognita eggs that hatched. Under greenhouse conditions, the CD 206 cultivar showed a 46.5% reduction in the number of galls, as well as fewer eggs in the soil and a lower RF. Similarly, in the CD 215 cultivar, the number of eggs was reduced and the RF was lower. These results indicate the potential for rosemary extract to control M. incognita in soybean crops.